2020
DOI: 10.1002/ejp.1686
|View full text |Cite
|
Sign up to set email alerts
|

Some like it hot: Preference for temperature and pungency consumption is associated with sensitivity to noxious heat

Abstract: BackgroundIndividuals vary in their temperature and pungency preferences; whereas some individuals prefer to bath in, or consume food and beverages at very high temperatures, others prefer lukewarm temperatures. Similarly, pungent food may be preferred by some, but not by others. The aim was to investigate, for the first time whether temperature and pungency preferences are associated with variations in thermal sensitivity or ethnic origin related to pungency consumption.Methods115 healthy volunteers participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…The overall spice levels (no heat/ mild, medium, spicy, very spicy) significantly differed by gender as well, CMH χ 2 = 12.6; p = 0.01 ( 35 ). As shown in Table 1 , Defrin, Logue, Smith, and Castillo-Carandang's findings also agreed with this trend, with males preferring a higher degree of spiciness compared with females ( 33 , 40 , 45 ). Alternatively, Stevenson and Yeomans ( 36 ) study found conflicting liking scores.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The overall spice levels (no heat/ mild, medium, spicy, very spicy) significantly differed by gender as well, CMH χ 2 = 12.6; p = 0.01 ( 35 ). As shown in Table 1 , Defrin, Logue, Smith, and Castillo-Carandang's findings also agreed with this trend, with males preferring a higher degree of spiciness compared with females ( 33 , 40 , 45 ). Alternatively, Stevenson and Yeomans ( 36 ) study found conflicting liking scores.…”
Section: Resultssupporting
confidence: 71%
“…But ethnicity, however, does not always predict spicy food use. One of Ludy and Mattes's ( 24 ) non-spicy food users was Asian American, and Defrin ( 40 ) found that subjects from different ethnic backgrounds in Israel did not differ significantly in their frequency of spicy food consumption, p = 0.15. These results suggest that spicy food consumption is high in some Asian countries, the US, and Mexico, but consumption frequency varies from person to person.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation